Cyclic di AMP phosphodiesterase nanovaccine elicits protective immunity against Burkholderia cenocepacia infection in mice - Wesam E. Gawad; Yosra I. Nagy; Tamer M. Samir; Ahmed Mohamed Ibrahim Mansour; Omneya M. Helmy (npj Vaccines)
Abstract Burkholderia cenocepacia causes life-threatening infections in immunocompromised patients. Treatment is challenging due to intrinsic antibiotic multiresistance, so vaccination provides an alternative approach. We aimed to identify vaccine candidates using reverse vaccinology and evaluate their efficacy as protein-loaded chitosan: pectin nanoparticles (C:P NPs) in a vaccine model. Applying strict subtractive channels, three proteins were shortlisted: WP_006481710.1 (LY), WP_012493605.1 (KT), and WP_006492970.1 (BD). Proteins were cloned, purified as His-tagged proteins, and loaded onto C:P NPs. Vaccinated mice had significantly higher systemic IgG and mucosal IgA antibody responses and induced IL-6 and IL-17A. 6x-His-LY-CS:P NPs and 6x-His-KT-CS:P NPs vaccines induced TNF-α. Vaccines conferred significant protection against B. cenocepacia intranasal infections. In conclusion, cyclic-di-AMP phosphodiesterase (WP_012493605.1) is a promising vaccine candidate that elicited IgG and IgA antibodies, Th1, Th2, and Th17 cellular immunity in BALB/c mice and protected against B. cenocepacia infection. This provides hope for saving lives of people at high risk of infection.